Underground parking lot at Turku market square : Zero energy parking hall and the biggest solar energy storage in the world - Lautkankare, Rauli; Salomaa, Nikolas; Martinkauppi, Birgitta; Slobodenyuk, Anna (EDP Sciences, 2020)
This paper opens the case Turku market square underground parking lot from the energy perspective. Also constructional and historical aspects are presented. Heavily populated city center has faced several challenges, such as intense traffic. Uncomfortable local tailpipe emissions and lack of parking spaces have decreased living conditions for the citizens and visitors. Therefore, total renovation of main market square of Turku was started in autumn 2018. Together with that, municipality should respond not only to primary needs, but also to national and global environmental targets. One of the new strategy objectives for Turku is being carbon-neutral city by 2029. Hence, project was based on large-scale renewable resources utilization for urban underground spaces. Research and analysis of possible technical solutions was made. Modern time is characterized by climate change and strong measures that need to be taken to stop the global warming. The heat, cold and electricity should be produced in a carbon neutral manner. This doesn’t exclude heated multilevel car parking facilities either. As the parking capacity grows and finding a free place is easier, a positive environmental effect is expected to be reached. The described underground parking lot in Turku is first of its kind in many ways: 1) Never before underground parking lot has dug up and constructed into clay-based soils in Finland, 2) it is probably the first zero carbon energy parking hall in Europe and 3) it has the biggest solar thermal energy storage in the world.
Keywords: fi=Sähkö- ja energiatekniikka|en=Electrical and Energy Engineering|